2016
DOI: 10.1103/physrevlett.117.143601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-Induced Macroscopic Superposition States in Cavity Optomechanics

Abstract: A novel protocol for generating quantum superpositions of macroscopically distinct states of a bulk mechanical oscillator is proposed, compatible with existing optomechanical devices operating in the badcavity limit. By combining a pulsed optomechanical quantum nondemolition (QND) interaction with nonclassical optical resources and measurement-induced feedback, the need for strong single-photon coupling is avoided. We outline a three-pulse sequence of QND interactions encompassing squeezingenhanced cooling by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 65 publications
(97 reference statements)
0
59
0
Order By: Relevance
“…This will necessitate involving a non-Gaussian element in the network, whether taking advantage of a non-Gaussian measurement, a non-linear optomechanical dynamics, or an already prepared nonGaussian resource. Promisingly in this direction, it has been shown that opto-and electro-mechanical systems can intrinsically host non-linearities in various settings [33,36,76,77], and this possibility has been suggested for engineering non-Gaussian states, dynamics, and measurements [32,[78][79][80][81][82][83][84][85]. The latter could potentially be exploited to unlock the universality of computation and this shall be the topic of future work.…”
Section: Discussionmentioning
confidence: 99%
“…This will necessitate involving a non-Gaussian element in the network, whether taking advantage of a non-Gaussian measurement, a non-linear optomechanical dynamics, or an already prepared nonGaussian resource. Promisingly in this direction, it has been shown that opto-and electro-mechanical systems can intrinsically host non-linearities in various settings [33,36,76,77], and this possibility has been suggested for engineering non-Gaussian states, dynamics, and measurements [32,[78][79][80][81][82][83][84][85]. The latter could potentially be exploited to unlock the universality of computation and this shall be the topic of future work.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, quantum entanglement between radiation and mechanical systems and also quantum squeezing of mechanical uncertainty have been demonstrated [14,16,17]. These experiments can be extended to prepare various quantum states of mechanical system [38][39][40][41][42][43][44][45]. To reach a high quality of transfer for any state of light to mechanical systems, universal interfaces have been proposed as well [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using a singlephoton detection event, entanglement between the vibrational states of two diamond crystals has been generated [38], and techniques for mechanical NOON state generation have been proposed [39,40], as well as schemes to entangle atomic ensembles with mechanical motion [41,42]. In addition, a scheme has been recently proposed that utilizes an optomechanical interaction with a nonclassical optical field prepared via photon subtraction to conditionally generate nonclassical mechanical states [43].…”
Section: Introductionmentioning
confidence: 99%